Drug Related Problems (DRPs) Penggunaan Antibiotik Profilaksis pada Bedah Ortopedi - Reiza, Zenita; Cholisoh, Zakky (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Drug Related Problems (DRPs) are treatment conditions that cause or have the potential to interfere with clinical outcomes and result in therapy failure. The use of prophylactic antibiotics often experiences inaccuracies that cause DRPs. The aim of this research was to determine the problems and causes of DRPs in the use of prophylactic antibiotics in clean orthopedic surgery patients using a retrospective approach. The inclusion criteria applied were clean orthopedic surgery patients aged >18 years. and exclusion criteria are patients with Diabetes Mellitus, immune diseases, and other infectious diseases and age > 60 years. The use of prophylactic antibiotics was analyzed based on the Regulation of the Minister of Health of the Republic of Indonesia concerning Guidelines for the Use of Antibiotics and then classified with PCNE V9.1. Of 264 medical records of orthopedic patients with clean surgery, the highest choice of prophylactic antibiotic therapy was ceftriaxone at 49.6%. The highest DRPs problems are related to safety issues (P2) 48.4% in the form of potentially harmful drugs occurring (P2.1), other problems (P3) 40% related to unnecessary drug administration (P3.1) and effectiveness 10.6% related to effects medication is not optimal (P1.2). The highest cause of DRPs, drug selection factor (C1) 67% (no drug indication (C1.2) = 36.7%, drug selection not in accordance with guidelines (C1.1) = 30.3%), drug use factor (C6) 24.9% in the form of an inappropriate administration time (C6.1), and dose selection factor (C3) 8.1% in the form of an inappropriate dose (C3.1). Keywords: Antibiotics, Prophylaxis, DRPs, PCNE, Orthopedics Surgery  ABSTRAK Drug Related Problems (DRPs) merupakan kondisi pengobatan yang menyebabkan atau berpotensi mengganggu hasil klinis hingga kegagalan terapi. Penggunaan antibiotik profilaksis seringkali mengalami ketidaktepatan yang menyebabkan terjadinya DRPs. Penelitian dilakukan bertujuan untuk mengetahui masalah dan penyebab terjadinya DRPs penggunaan antibiotik profilaksis pada pasien operasi bersih ortopedi dengan pendekatan retrospektif. Kriteria inklusi diterapkan yaitu pasien operasi bersih ortopedi yang usia >18 tahun. dan kriteria eksklusi adalah pasien dengan Diabetes Mellitus, penyakit imunitas, dan penyakit infeksi lainnya serta usia >60 tahun. Penggunaan antibiotik profilaksis dianalisis berdasarkan Peraturan Menteri Kesehatan Republik Indonesia tentang Pedoman Penggunaan Antibiotik kemudian diklasifikasikan dengan PCNE V9.1. Dari 264 rekam medik pasien ortopedi dengan tindakan operasi bersih, pemilihan terapi antibiotik profilaksis tertinggi adalah ceftriaxone sebesar 49,6%. Masalah DRPs tertinggi terkait masalah keamanan (P2) 48,4% berupa obat merugikan berpotensi terjadi (P2.1),  masalah lain (P3) 40% terkait pemberian obat yang tidak perlu (P3.1) dan efektivitas 10,6% terkait efek obat tidak optimal (P1.2). Penyebab DRPs tertinggi, faktor pemilihan obat (C1) 67% (tidak adanya indikasi obat (C1.2) = 36,7%, pemilihan obat yang tidak sesuai dengan pedoman (C1.1) = 30,3%),faktor penggunaan obat (C6) 24,9% berupa waktu pemberian yang tidak sesuai (C6.1), dan faktor pemilihan dosis (C3) 8,1% berupa dosis yang tidak tepat (C3.1). Kata Kunci: Antibiotik, Profilaksis, DRPs, PCNE, Operasi Ortopedi